Agent Orange The Failure of Science, Policy and Common Sense - Young, Alvin L. (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book tells the story of Agent Orange, its usage and the policies that surround it. Agent Orange contains a contaminant known as TCDD. It was the most widely used defoliant from 1965 - 1970 and became one of three major tactical herbicides used in Vietnam. More than 45 major health studies were conducted with Vietnam veterans from the United States, Australia, New Zealand, and Korea seeking a relationship between veterans' health and TCDD. Allegations of birth defects in the families of Vietnam veterans and the Vietnamese represented a case study in propaganda and deliberate misinformation by the government of Vietnam. The Policies of the US Government implemented by Congress and the Department of Veterans Affairs (DVA) identified 17 recognized associated presumptive diseases that failed the tests of "cause and effect" and common sense. This book tells the story of Agent Orange, its usage, the health studies and those policies from a diverse range of perspectives, delving into science, statistics, history, policy and ethics. It is of interest to scholars engaged in history, political and social philosophy and ethics.
1. The Herbicide Orange Primer -- 2. Project RANCH HAND: The Men and The Mission -- 3. Update on History and Science of the Major Components of Agent Orange -- 4. Update on Picloram and Agent White -- 5. Update on Dimethylarsenic Acid, The Major Component of Agent White -- 6. The Environmental Fate of the TCDD Associated with Agent Orange -- 7. Acquisition, Transport, and Disposal of the Drums Used for Tactical Herbicides Sent to South Vietnam -- 8. Human Exposure to Aerial Dispersion of Agent Orange and TCDD -- 9. Health Studies of Vietnam Veterans -- 10. Health Studies of Vietnamese -- 11. Birth Defects: Facts, Fiction, and Propaganda -- 12. The Media and Agent Orange -- 13. Failure of Science and Common Sense -- 14. The Failure of Policy and Common Sense.
Keywords: Technology; History; Technology-Moral and ethical aspects; Politics and war; History of Technology; Ethics of Technology; Military and Defence Studies